Nativization of English in Malaysia and the Philippines as seen in English dailies - David, Maya Khemlani; Dumanig, Francisco Perlas (2008)
There is a strong trend of nativization of English in Malaysia and the Philippines. This research examines data from English newspapers in two Asian countries in order to determine the extent of nativization of local varieties of English. The papers examined were The Star (Malaysia), Philippine Daily Inquirer , and Manila Bulletin (Philippines). The borrowing and assimilation of a large number of lexical items in the English dailies in these two countries were analyzed and categorized. These lexical items were found in various categories, such as people, events, cultural activities, places, political movements, religion, arts/films, food, clothes, and quotations. The borrowing and switching to local lexis in English dailies demonstrate the nativization of English in these dailies.
Includes bibliographical references (pages 77-79).